Language attitude of Singkil students in the context of bilingualism: a study of sociolinguistics - Dedy Suhery; Rahmatsyah Rangkuti; Zahratul Idami (Politeknik Negeri Bali, 2022)
This paper attempts to look at Singkil students’ attitudes towards their language (Singkil language) and their attitudes towards Bahasa Indonesia as the national language of the Indonesian country. Singkil language is an Austronesian language spoken by aboriginal speakers living dominantly in five districts, namely Kuta Baharu, Simpang Kanan, Suro, Gunung Meriah, and Singkil that are administratively under the Singkil regency of Aceh province, Indonesia. According to Ethnologue, Singkil is a dialect of Batak Alas-Kluet (btz). The method used in this research is descriptive. Data were obtained through a quantitatively analyzed questionnaire for each characteristic feature calculated the average number of values (mean) language attitudes, using a Likert technique. The language attitude of respondents here towards Singkil language is very positive. It can be seen from the 12 questions given are mostly in positive attitude from 2,7 – 4,8. Otherwise, question 8 and 9 are negative from 2 – 2, 5. Therefore, the Singkil students have a positive attitude toward the use of their language. On the other hand, the language attitude of Singkil students towards bahasa Indonesia from 12 questions given are mostly in positive attitude from 2,8 – 4,6. Otherwise, question 5, 12, and 12 are negative from 2 – 2, 3. Therefore, the Singkil students have a positive attitude toward the use of bahasa Indonesia. Thus this study hopefully may reveal how the people of Singkil in several areas extensively use bahasa Indonesia in their daily communication, and the government of Aceh Province should maintain the sustainability of language in Aceh Province especially Singkil language by showing the uniqueness and richness of linguistics diversity in the region.